The Impact of Supply Chain Integration on Financial Performance of the Firm - Antora, Nusrat Jahan; Raihan, Zohir (European Journal of Applied Sciences, 2024)
Supply Chain Integration (SCI) is widely acknowledged as a strategic process that significantly contributes to positioning organizations favorably for improved firm performance. This study delves into the relationship between financial performance and supply chain integration, focusing on the impact of various integration strategies, including internal control, supplier integration, customer integration, and internal integration, on a business's financial performance. Through Regression, Reliability, and Correlation analyses conducted on an 80-respondent survey, correlations between the variables were examined. The findings reveal a substantial and positive influence of SCI on a company's financial success. Further analysis of individual dimensions indicates that customer integration yields the most significant positive effect on financial success. Moreover, notable correlations were observed between supplier integration and financial performance, internal control and financial performance, and internal integration and financial performance. While each variable demonstrates a statistically significant impact, customer integration emerges as the most influential factor. This study underscores the relationship between information flows and financial performance, underscoring the benefits of integration resulting from knowledge development. Supply chain experts can leverage these research findings to enhance their business's bottom line.